Pembuatan Digital Elevation Model Universitas Palangka Raya Menggunakan Drone dan GPS Geodetik - Raden Seandy Novaryansyah Pradana Putra; Desi Riani; Sutan Parasian Silitonga (Program Studi Teknik Sipil Fakultas Teknik Universitas Palangka Raya, 2023)
The Digital Elevation Model (DEM) contains elevation and slope information, making interpretation easierso that it is a fundamental element of geospatial data and can be used as a mapping source. The use oftechnology in the field of photogrammetric mapping is demonstrated by the use of Unmanned Aerial Vehicle(UAV) or drones in mapping and Geodetic GPS tied to benchmarks to obtain Ground Control Point (GCP)coordinates as ground control points. This research aims to make the Palangka Raya University DEM usingUAV and Geodetic GPS. In processing aerial photo data, the photogrammetric method is used. The time fortaking aerial photo data begins on 14-21 October 2022 which is divided into 10 flying missions with a flightaltitude of 100 m, overlap and sidelap of 75%, and camera angle of 90 with a total of 7,935 photos. GCP dataretrieval using the Real Time Kinematic (RTK) method with Geodetic GPS was carried out on October 14,2022 with a total of 33 coordinate points. The DEM that has been formed can be seen that mapping usingUAVs/drones and Geodetic GPS produces high-resolution photo data that can be used for making DigitalElevation Models (DEMs) with the highest altitude at Palangka Raya University, namely 90 meters and thelowest altitude at 50 meters. The DEM resolution obtained is 18.1 cm/pixel and the interpolation point densityis 30.7 points/m2.